Investigating the role of neuronal hyperactivity in stress susceptibility and brain beta‐amyloid deposition. (20th December 2022) - Rogers, Annika; Sharp, Elizabeth; Razlighi, Ray; Oh, Hwamee
Abstract: Background: Both animal and human literature have suggested a relationship between stress responses and an increased susceptibility to extracellular beta‐amyloid (Aβ) plaque aggregation, one of the pathological features of Alzheimer's Disease (AD), as well as clinical symptoms of AD. Despite this evidence, a neuro‐mechanistic pathway that underlies the relationship between the psychological stress response and brain Aβ pathology remains poorly understood. We examined the hypothesis that increased stress responses are associated with neuronal hyperactivity and increased brain Aβ deposition along the spectrum of AD. Method: We included 35 Cognitively Normal (CN) and 21 Significant Memory Concern (SMC) individuals and 81 patients with Mild Cognitive Impairment (MCI), and 29 AD patients from the Alzheimer's Disease Neuroimaging Initiative (ADNI). Neuropsychiatric Inventory (NPI‐Q) total scores were used to indicate stress responses. The amplitude of low frequency fluctuations (ALFF) was calculated using resting‐state fMRI (rsfMRI) scans as a measure of neuronal activity. AV45‐SUVR measures were downloaded from the ADNI study. In SPM12, general linear models were performed on normalized ALFF maps to examine the associations of stress responses and brain Aβ deposition with neuronal activity, while controlling for age, sex, and APOE4 carrier status. Result: NPIQ scores were significantly associated with brain Aβ indices across the entire cohort spanning from cognitively normal (CN) older adults to AD patients. The CN group exhibited significant increases in ALFF in the anterior cingulate, caudate, and inferior occipital cortices in relation to increased NPI‐Q scores, while AD participants exhibited decreased ALFF in multiple regions including medial and lateral frontal cortices. Moreover, with higher brain Aβ load, CN participants showed increased ALFF in medial and lateral frontal cortices, while AD participants showed decreased ALFF in medial frontal, temporo‐parietal junction, and inferior parietal cortices. Conclusion: These results indicate a potential link between heightened stress responses and increased susceptibility to the development of AD pathologies through neuronal hyperactivity, especially in the early stages of AD. These findings provide neural mechanisms underlying the relationship between stress as a risk factor for AD by highlighting the role of neuronal hyperactivity in this association, while validating the use of rsfMRI for these analyses.